Valery Gergiev conducts Prokofiev Alexander Toradze performs the 2nd piano concerto : Moscow Easter Festival - Prokofiev, Sergey 1891-1953; Prokofiev, Sergey 1891-1953; Prokofiev, Sergey 1891-1953 (Idéale Audience, 2012)
In Moscow, second part of the four concerts dedicated to Prokofiev by the Mariinsky Theatre Orchestra and Valery Gergiev. Valery Gergiev conducts a festive programme at the Moscow Easter Festival: the 2nd and 3rd symphonies by the Russian composer and the Piano Concerto No. 2. He invites the Georgian pianist Alexander Toradze to come and perform with him (an artist with whom he notably recorded the complete Prokofiev concertos). Starting each year on Easter Sunday (according to the Julian calendar), the Moscow Easter Festival not only features great concerts with the Mariinsky Theatre Orchestra and music director Valery Gergiev, but also internationally renowned soloists. In 2012, the festival -- dedicated to Sergei Prokofiev -- invited the pianists Daniil Trifonov (1st prize at the Tchaikovsky Competition in 2011 and third prize at the Chopin Competition in 2010), Alexander Toradze (familiar to Gergiev), Alexei Volodin (a former student of the Moscow Conservatory) and the American-Armenian pianist Sergei Babayan. Over the past 20 years spent at the head of the Mariinsky Theatre Orchestra, Valery Gergiev has clearly expanded one of the most prestigious Russian orchestras' repertoire. Their interpretations of Prokofiev have become legendary, not only because Gergiev has recorded most of the composer's masterpieces, but also because he has contributed in promoting the rarest pieces Prokofiev has ever written. This series of concerts, programmed as part of the 11th anniversary of the Moscow Easter Festival, display complete Prokofiev symphonies, but also four of his Piano concertos, along with excerpts from the composer's great ballets (Cinderella and Romeo and Juliet). This concert was broadcast live on medici.tv
Keywords: Symphonies; Concertos (Piano); Webcast; Internet videos; Vidéos sur Internet